Turkey : Gas Sector Strategy Note - World Bank (Washington, DC, 2013)
This report summarizes a strategy for accelerating the liberalization of the natural gas market in Turkey in line with the objectives of the Natural Gas Market Law of 2001 (Law 4646). It focuses on the desired future framework for the natural gas market and indicates the changes that need to be made in the "buy" function, "sell" function, and transit function as well as the steps that need to be taken to transition from the current framework to the desired framework.